Optimization of concrete mixture compositions with a superplastifier additive as well as a binary microwave (Международный научный журнал «Инженер», 2026)
The article analyzes the role of composite binders in improving the operational characteristics of highqualityconcrete. It highlights the impact of materials such as fly ash, slags, and polymers on the quality,strength, and durability of concrete. The potential for improving concrete quality through the application ofthese technologies in Uzbekistan's construction industry is also discussed. In practice, CEMI 32.5 N andbased on B15, B20 and B30 class concrete are mainly used for building buildings and structures, for themanufacture of prefabricated and monolithic concrete and reinforced concrete objects and structures. As anoptimized parameter, the strength of the concrete stored for 28 days under normal conditions was obtained.Zero levels are chosen in such a way that the optimized parameter takes the best values of the consistency.Special attention was paid to the production of new technologies, especially concrete, reinforced concreteand polymer materials. The concrete industry has improved the strength, corrosion resistance andenvironmental safety of concrete with the help of composite materials, polymers, nanomaterials and otherinnovative additives.